1981
DOI: 10.1111/j.1365-2559.1981.tb01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis cystica profunda

Abstract: Fourteen cases of gastritis cystica polyposa, four gastric adenomas and 25 "mature" erosions removed by diathermy at endoscopy were studied by light microscopy. Twenty surgical resections from gastric cancer patients and 18 gastric resections from gastroenterostomy patients previously operated upon for benign lesions were also studied. The mucosa showed consistent changes which were grouped as "gastritis cystica superficialis". Most surgical specimens, three out of 25 "mature" erosions, the four adenomas, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 16 publications
1
78
1
2
Order By: Relevance
“…In most cases, gastritis cystica profunda develops in patients who have undergone gastroenterostomy, with or without gas− tric resection, and the lesion usually ap− pears on the gastric side of the anastomo− sis [1]. It is rarely discovered in an unop− erated stomach [2].…”
mentioning
confidence: 99%
“…In most cases, gastritis cystica profunda develops in patients who have undergone gastroenterostomy, with or without gas− tric resection, and the lesion usually ap− pears on the gastric side of the anastomo− sis [1]. It is rarely discovered in an unop− erated stomach [2].…”
mentioning
confidence: 99%
“…It was initially recognized in 15 cases that presented by Franzin (1981). Laratte et al (2012) have reviewed this condition and have mentioned that 37 cases have been reported in the English literature.…”
Section: Figure 3: Pathological View Of Gcp (Hematoxylin and Eosin mentioning
confidence: 99%
“…The histological findings of cystic glandular inclusions with a connective tissue laden submucosa were first described by Littler and Gleibermann in 1972 [1]. However, it was not until 1981 that Franzin and Novelli coined the term "gastritis cystica profunda," and described fifteen cases of GCP that were initially confused with other gastric pathologies, such as mature erosions and gastric adenomas [2]. Since that time, very few additional cases of GCP have been reported, and in these instances GCP was initially thought to represent Ménétrier's disease, [3][4][5] gastric adenocarcinoma, [6,7] inverted hyperplastic polyps, [8] and other pathologies.…”
Section: Introductionmentioning
confidence: 99%